Pronoun in “The Case of the Wrecked Room”. - Zainuddin Saragih (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract The researcher focuses the study on Pronoun in “The Case of the Wrecked Room”. Which is existed in English is Fun (book). The research is done through descriptive qualitative, in which the aims of the research are to describe Preposition in “The Case of the Wrecked Room”. Which is existed in English is Fun (book). The analysis is done through kinds of Pronoun; Personal Pronoun, Demonstrative Pronoun, Relative Pronoun, Interrogative Pronoun, Reflexive Pronoun, Indefinite Pronoun, and Reciprocal Pronoun. Additionally, here the researcher tries to determine the dominant use of kinds of Pronoun. Consequently, the researcher takes “The Case of the Wrecked Room ” for primary data, and then some related Journals and books about Pronoun. Furthermore, the researcher uses content analysis method for analyzing the data. There the technique of analyzing the data; Reading the short story “The Case of the Wrecked Room”. Signing kinds of Pronoun in “The Case of the Wrecked Room”, and then giving found kinds of Pronoun explanations. Finally, having conclusion of overall discussion. In conclusion, there are 25 Pronouns in “The Case of the Wrecked Room” in English is Fun (book), by: David L. Larcom. There are ten for Personal Pronoun, seven for Demonstrative Pronoun, two for Relative Pronoun, one for Interrogative Pronoun, zero for Reflexive Pronoun, four for Indefinite Pronoun, and one for Reciprocal Pronoun. Keywords: Wreck, Pronoun, Dominant